COVID-19’s Effect on Indian MSMEs: Insights from Stakeholders - Ahmad, Alam; Akram, Hafiz Wasim; Akhtar, Samreen; Choudhary, Pooja; Kumar, Neeraj (International Journal of Economics and Financial Issues, 2024)
Indian MSME (Micro, Small and Medium Enterprises) sector, an invaluable employment generator with a cluster of more than 63 million enterprises, is deeply dented by the noxious coronavirus. The second most significant sector of the Indian economy regarding employment creation is in jeopardy after the Covid-19. The sudden abject degradation of performance and eventual threat to the existence of MSME not only captivates the attention but also sets in disquietude in mind to fathom the inherent causes of this fragility and excogitate the ways and means of saving them. Against this background, proper diagnosis of the effect of Covid-19 on MSMEs is inevitable. The analysis is based on Qualitative as well as secondary data. Qualitative data has been collected through semi-structured interviews with 48 MSME stakeholders selected by Judgmental Sampling. The research finds significant challenges before MSME that must be tackled to salvage the industry from an imminent existential threat. The paper recommends the adoption of Industry-4.0 and the closure of gaps identified in the paper to give saving breath to the financially beleaguered and faltering sector. During the last few years, Covid-19 has grabbed literature positioning galore, but they are not specific to Indian MSME. This study is an attempt to gauge the obstacles, measures and gaps faced by Indian MSME post COVID scenario.